Opportunities to empower students entrepeneurship in TUBE@IPT - Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 13 November 2022 - Universiti Malaysia Pahang (UMP) today received a delegation visit from SME Corp. Malaysia in its visit session to learn about the development of the participants of Tunas Usahawan Belia Bumiputera (TUBE@IPT) in UMP.